The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/jat.1424
|View full text |Cite
|
Sign up to set email alerts
|

Differential mRNA expression of acetylcholinesterase in the central nervous system of rats with acute and chronic exposure of sarin & physostigmine

Abstract: A time-course study was carried out to measure the acetylcholinesterase (AChE) gene expression in the brain of female rats exposed to different doses of sarin and physostigmine. Short-term effects were studied with an acute single subcutaneous dose (s.c.) of 80 microg kg(-1) (0.5 x LD(50)) sarin. Cortex and cerebellum showed a significant decline in AChE mRNA expression at 2.5, 24 and 72 h. Biochemical studies showed that plasma butrylcholinesterase (BChE) and brain AChE activities were significantly decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…agent similar to rivastigmine, such as physostigmine, may also induce a feedback response of AChE expression either (27). No significant differences were noticed for BChE activities either in plasma or in CSF in the donepezil-treated patients, hence confirming the specificity of donepezil action against AChE (5).…”
Section: Discussionmentioning
confidence: 58%
“…agent similar to rivastigmine, such as physostigmine, may also induce a feedback response of AChE expression either (27). No significant differences were noticed for BChE activities either in plasma or in CSF in the donepezil-treated patients, hence confirming the specificity of donepezil action against AChE (5).…”
Section: Discussionmentioning
confidence: 58%
“…The same brain cerebral cortex region was examined in both control and exposed mice. b A 350% increase in GFAP reactive astrocytes (at 150 days) in the cerebral cortex of GW agent-exposed mice as compared to control mice, P \ 0.05 observed in studies showing that after 30 days of PB and sarin exposure, there is an increase in AChE mRNA levels in the cortex (Bansal et al 2009). An electrophysiology study of insect larvae showed that combined exposure to PER and Propoxur (another carbamate AChE inhibitor), at maximum tolerable concentration, resulted in a synergistic increase in membrane depolarization, which was evidenced by a reduction in the amplitude of the excitatory postsynaptic potential (EPSP), indicative of an increase in synaptic ACh (Corbel et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…However, long-term consequences of combined exposure to PB and PER may include lowered synaptic ACh levels. This is supported by studies showing that following exposure to these and similar chemicals, there is a compensatory increase in AChE expression and/or activation of muscarinic acetylcholine receptors (mAChRs) pathways that downregulate ACh production (Corbel et al 2006;Bansal et al 2009). Animal studies show that combined exposure to PB and PER can produce sensorimotor deficits, neuronal death, astrogliosis and AChE inhibition and reduced ligand binding of muscarinic receptors in several different brain regions of exposed rats Abdel-Rahman et al 2002).…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that a convulsant dose of soman immediately inhibits brain cholinesterase with maximum inhibition within 10 min and a large increase in ACh concentration at the time of seizure initiation. Furthermore, previous studies have shown an immediate induction of AChE mRNA expression levels in the rat brain following sarin exposure [37,38]. If seizures are not immediately stopped, a transition phase occurs 5-40 min post-exposure where other neurotransmitter systems are perturbed.…”
Section: Discussionmentioning
confidence: 98%